2014
DOI: 10.22599/bioj.78
|View full text |Cite
|
Sign up to set email alerts
|

Oculocutaneous albinism: an African perspective

Abstract: Aim: To describe the genetics behind oculocutaneous albinism (OCA), and explore OCA in an African context in terms of the effects on the health and education of individuals with OCA. Methods: A literature-based review was conducted using Pubmed. Searches were restricted to Englishbased publications, focusing on OCA in Africa. Results: The genetics behind OCA and the effects of OCA in terms of visual impairment and skin cancer are explained along with a description of what low vision services and low vision aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Research has shown that OCA is the most common form of albinism in many parts of Africa (Cruz-Inigo, Ladizinski, & Sethi, 2011;Kromberg et al, 2012). The incidence and prevalence of albinism in Africa varies between and within countries, and there are variations in the treatment of PWA in Africa (Mcbride, 2014), with various studies reporting on violence against and attacks on PWA in some African countries (Cruz-Inigo et al, 2011;Franklin, Lund, Bradbury-Jones, & Taylor, 2018;Ikuomola, 2015). For example, Baker, Lund, Nyathi, and Taylor (2010) described instances where PWA in South Africa and Zimbabwe were killed or left to die by their families because of the social stigma associated with their condition.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that OCA is the most common form of albinism in many parts of Africa (Cruz-Inigo, Ladizinski, & Sethi, 2011;Kromberg et al, 2012). The incidence and prevalence of albinism in Africa varies between and within countries, and there are variations in the treatment of PWA in Africa (Mcbride, 2014), with various studies reporting on violence against and attacks on PWA in some African countries (Cruz-Inigo et al, 2011;Franklin, Lund, Bradbury-Jones, & Taylor, 2018;Ikuomola, 2015). For example, Baker, Lund, Nyathi, and Taylor (2010) described instances where PWA in South Africa and Zimbabwe were killed or left to die by their families because of the social stigma associated with their condition.…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity and mortality linked to skin cancers, discrimination, stigmatization, and school dropouts due to vision problems are still high with a scarcity of preventative and curative measures. (McBride, 2014).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…in the skin is to absorb ultraviolet (UV) light and prevent damage. Without melanin the skin is more prone to sunburn and skin cancer" [3]. In addition, "lack of melanin results in a triad of signs which is pale skin, light hair, and pale iris colour.…”
Section: Original Research Articlementioning
confidence: 99%
“…The study explores the life experiences of people with albinism in Gaborone, Botswana and the misconceptions of societies towards such people [1,2]. "Derived from the Latin word 'albus' meaning 'white', oculocutaneous albinism (OCA) is a relatively rare genetic disorder in which the body does not biosynthesize melanin" [3]. "Melanin is a photo protective protein whose role…”
Section: Introductionmentioning
confidence: 99%